The professional relationship forms the base: Swedish child health care nurses’ experiences of encountering mothers exposed to intimate partner violence - Agneta Anderzén Carlsson (Taylor & Francis Group, 2021)
Purpose This study aimed to explore child health care nurses’ clinical experiences from encounters with mothers exposed to intimate partner violence (IPV), as little research has explored this topic. Method Nine child health care nurses from two Swedish regions were interviewed. The interviews were analysed using thematic analysis. Results The narratives depicted the nurses’ strong commitment to, and professional relationship with, the exposed mothers. The experience of working as a nurse and having encountered IPV in clinical practice made the nurses more confident, which impacted their performance and attitude towards this topic. The ability to uphold the professional relationship was threatened by lack of support and interprofessional collaborations. Conclusions The professional relationship was central to the encounters, yet could impose an emotional burden on the nurses. While the nurses wanted to improve their knowledge of the process around the mother and child, they were happy to pass the primary responsibility over to other professionals. The findings highlight the challenge in establishing sustainable support for nurses, and building a transparent collaboration process between the health care sector and the social services, serving the well-being and safety of the mother and child.